Moving from evidence to practice: Models of care for the prevention and management of musculoskeletal conditions - Speerin, R.; Slater, Helen; Li, L.; Moore, K.; Chan, M.; Dreinhofer, K.; Ebeling, P.; Willcock, S.; Briggs, Andrew (Bailliere Tindall, 2014)
With musculoskeletal conditions now identified as the second highest cause of the morbidity-related global burden of disease, models of care for the prevention and management of disability related to musculoskeletal conditions are an imperative. Musculoskeletal models of care aim to describe how to operationalise evidence-based guidelines for musculoskeletal conditions and thus support implementation by clinical teams and their health systems. This review of models of care for musculoskeletal pain conditions, osteoarthritis, rheumatoid arthritis, osteoporosis and musculoskeletal injuries and trauma outlines health system and local implementation strategies to improve consumer outcomes, including supporting access to multidisciplinary teams, improving access for vulnerable populations and levering digital technologies to support access and self-management. However, the challenge remains of how to inform health system decision-makers and policy about the human and fiscal benefits for broad implementation across health services. Recommendations are made for potential solutions, as well as highlighting where further evidence is required.